A study of emotional labour of fast food employees - Ghazali, Hazrina; Abdul Halim, Nurhasmilaalisa; Yap, Sing Yee (2012)
This study aims to investigate the level of agreement on emotional labour strategies that include standard scripts, dress code and acting. A survey questionnaire used to underpin this study and 170 respondents participated in this study. Data were analysed by using SPSS and findings found that the use of standard scripts, dress code and acting had from moderate to high level of agreement on employees’ emotion. Results also found that standard scripts helped employees to better understand about customers and improve their social skills. Fast food employees agreed that dress code enable them to be more sociable and lead more strengths than weakness. Results also revealed that acting assisted fast food employees to satisfy the customer requirements.